Investment and Decision Analysis on Financing Models for Solar Panel Project by British American Tobacco Indonesia - Kurniawan, Feri (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The research aims to analyze the most viable financing model for British American Tobacco's (BAT) Indonesia solar panel project to meet the ESG target of 50 percent CO₂ emission reduction by 2030. Key challenges include high initial investment, low ROI, and long payback period. The research used a mixed methods approach, that is interviews and FGDs generated decision criteria, which were translated into quantitative analysis using Kepner-Tregoe Decision Analysis and Analytical Hierarchy Process (AHP). The results indicated the leasing model as the best alternative, and TOTAL Solar Indonesia as the most suitable supplier. Kepner-Tregoe Potential Problem Analysis (KT-PPA) was conducted to anticipate long-term contract risks, such as default and taxation. This research provides an optimal financing implementation strategy, best supplier selection, and risk mitigation for BAT Indonesia's renewable energy projects.